Factors Effecting Employees Motivation: A Study of the Ministry of Foreign Affairs in Myanmar - Htet Aung Kyaw; Vasu Keerativutisest (My University, 2023)
The study aimed to determine the organizational factors that influence employee motivation in the Ministry of Foreign Affairs in Myanmar. Organizational factors as the independent variable were hypothesized to influence the dependent variable. Organizational factors are organization policies, salary, compensation and bonus, working conditions, job security, interpersonal relationships, psychological conditions, and emotional intelligence directly affect employee motivation. This research employed a mixed method that collects the qualitative data first and the results from the qualitative data analysis use the questionnaires for the quantitative data collection. Descriptive statistics of dependent and independent variables are obtained to interpret the responses of participants and draw comparisons of how the responses are distributed. Multiple regression and Pearson correlation coefficient were applied to test hypotheses. Organizational commitment as a moderating variable can strengthen the relationship between organizational factors and employees' motivation. Testing of the hypothesis found that organization factors significantly influence employees' motivation and organizational commitment can modify the relationship between organization factors and employees' motivation
Keywords: Job Satisfaction and Organizational Behavior; Islamic Finance and Banking Studies